Simulation Study of Energy Dissipation Efficiency of Tesla Energy Dissipation Device in High-Pressure Oil and Gas Pipeline - Li, Yuxuan (Scientific Journal of Technology, 2025)
Based on the standard -  model and multiphase flow model, numerical simulations were used to study the effects of inlet pressure, fluid components and different numbers of cascade stages on the energy dissipation efficiency of Tesla dissipation devices in high-pressure oil and gas pipelines. The simulation results show that: In the general pressure range of high-pressure oilfield recovery fluids, with the increase of inlet pressure, the single-stage Tesla energy dissipation device's energy dissipation efficiency with the increase of inlet pressure shows a gradual increase in the trend of inlet pressure, and the larger the inlet pressure, the more obvious energy dissipation effect. In the case of a certain inlet pressure, the single-stage Tesla energy dissipation device for the different flow media from high to low energy dissipation efficiency is: oil, oil-water mixed media, water. And in the oil-water mixing medium, The greater the proportion of oil, the better the energy dissipation effect; At a constant inlet pressure, the dissipation efficiency of the Tesla energy dissipation device increases gradually with the number of stages in series, but the value of the pressure drop produced by each stage tends to decrease gradually as the number of stages of the energy dissipation device increases. Taking into account the effect of energy dissipation and economic efficiency, it is determined that the optimal number of series connection stages for energy dissipation device is 4.